2018
DOI: 10.1007/s00442-018-4097-3
|View full text |Cite
|
Sign up to set email alerts
|

Both plant genotype and herbivory shape aspen endophyte communities

Abstract: Salicinoid phenolic glycosides are common defence substances in salicaceous trees and specialist leaf beetles use these compounds for their own defence against predators. Salicinoids vary qualitatively and qualitatively in aspen (Populus tremula) and this variation has a genetic basis. The foliar endophyte mycobiome is plentiful and we hypothesised that it is related to plant genotype, potentially mediated by salicinoid composition, and that interactions with the leaf beetle Chrysomela tremula may alter this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 67 publications
(103 reference statements)
4
26
1
Order By: Relevance
“…This suggests that the twig fungal communities of F. excelsior genotypes responded differently to the seasonal variables, which could be due to certain fungal taxa governing resistance to ash dieback in the resistant genotypes or vice versa. This is similar to previous findings in other tree species, for example, aspen (Populus tremula) (Albrectsen et al, 2018), narrowleaf cottonwood (P. angustifolia) (Lamit et al, 2014) and coffee (Coffea arabica) (Saucedo-Garcia et al, 2014). Furthermore, we also detected a significant effect of susceptibility to ash dieback on the twig fungal communities of F. excelsior genotypes.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that the twig fungal communities of F. excelsior genotypes responded differently to the seasonal variables, which could be due to certain fungal taxa governing resistance to ash dieback in the resistant genotypes or vice versa. This is similar to previous findings in other tree species, for example, aspen (Populus tremula) (Albrectsen et al, 2018), narrowleaf cottonwood (P. angustifolia) (Lamit et al, 2014) and coffee (Coffea arabica) (Saucedo-Garcia et al, 2014). Furthermore, we also detected a significant effect of susceptibility to ash dieback on the twig fungal communities of F. excelsior genotypes.…”
Section: Discussionsupporting
confidence: 91%
“…Rajala et al [60] demonstrated variations in the communities of endophytes between Norway spruce clones, which suggests a potential influence of the host tree genotype. Albrectsen et al [146] further confirmed that the foliar endophyte composition of Populus tremula L. is influenced by the host genotype. These observations indicate that foliar endophytes communities vary not only among diverse host species [86,135,138], but also among genotypes of the same species [60,146].…”
Section: Aerial Endophytesmentioning
confidence: 87%
“…Lastly, there has been increasing interest in the effects of chemical variation on plant-herbivore-microbe interactions (Tabata 2018), and here Albrectsen et al (2018) show that the composition of tree endophytic fungi is influenced by both host tree genotype and leaf beetle herbivory. It is notable that herbivory enriches fungal assemblages without relation to the plant genotype.…”
Section: Responses Of Herbivores and Other Organisms To Plant Variationmentioning
confidence: 99%
“…The studies of this special topic cover a broad range of plant life forms, from marine algae in an aquatic system (Ledet et al 2018) to terrestrial herbs (Calf et al 2018;Chiriboga et al 2018;Cuny et al 2018;Howard et al 2018;Humphrey et al 2018;Kergunteuil et al 2018;Quintero and Bowers 2018), to shrubs (Nell et al 2018;Ochoa-López et al 2018), to long-lived trees (Albrectsen et al 2018;Bagchi et al 2018;Cipollini and Peterson 2018;Coley et al 2018;Falk et al 2018;Lämke and Unsicker 2018). In twelve case studies and four review papers, selected aspects of the huge variation in phenomena and underlying mechanisms are highlighted and new research questions opened, which may inspire further research in this exciting field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation